PENGARUH INTEGRASI NILAI-NILAI ISLAM MELALUI PENDEKATAN IMAN DAN TAQWA (IMTAQ) PADA HASIL BELAJAR SISTEM REPRODUKSI MANUSIA DI MAN 2 KOTA BANDUNG - Iwan Ridwan Yusuf; Ukit Ukit; Epa Paujiah (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2018)
Basically, education is a structured and systematic pattern that aims to improve human civilization, including biology teaching which is expected to contribute to the improvement of student behavior. Therefore, it is necessary to integrate religious values ​​as an important part in biology lessons. This research aims to know the effect of applying faith and taqwa (IMTAQ) approach to Biology learning in improving meaningful learning, with learning outcomes in the form of conceptual mastery and affective improvement. The research was conducted by using quasi experimental method, which is expected to describe phenomenon, occurrence, and causal relationship as the impact of integritation value of religious on biology subjects in the school of MAN 2, Bandung. In the research focus, it is assumed that teachers have the ability to integrate general science materials with Islamic values. The results showed that the integration of Islamic values ​​through IMTAQ approach can improve the process and the students learning outcomes, significantly. Used of this approach can also improve teacher performance with three reasons; 1) learning time more effective and efficient, 2) learning more focused on analysis of study of general and religious knowledge, and 3) learning activities more controlled. Through this model, the acquisition of learning outcomes has increased the mastery of significant student concepts, as evidenced by the increasing grade of students of class XI IPA from pre-test (36) and post-tests (74) results, with N-Gain 0.58 (medium category). The average post-test score indicates that 80% have reached of KKM (70), whereas affective indicator is 4.24% (high qualification). This study demonstrates that the integration of Islamic values ​​through an approach of faith and taqwa in biology learning can improve the meaningfulness of learning, and similar concepts can be implemented in other subjects and other schools.